Contemporary Chicana poetry : a critical approach to an emerging literature - Sánchez, Marta Ester (University of California Press, 1985)
Discusses 4 Chicana poets' "dilemmas of their dual relationship to American and Mexican societies and of their dual identity as Chicanas and as women writing in a contemporary setting."
Keywords: American poetry -- Mexican American authors -- History and criticism.; American poetry -- Women authors -- History and criticism.; American poetry -- 20th century -- History and criticism.; Mexican American women in literature.; Spanish poetry -- Mexican American authors -- History and criticism; Spanish poetry -- Women authors -- History and criticism; Spanish poetry -- 20th century -- History and criticism; Poésie américaine -- Auteurs américains d'origine mexicaine -- Histoire et critique.; Poésie américaine -- 20e siècle -- Histoire et critique.; Poétesses américaines d'origine mexicaine.; Américaines d'origine mexicaine dans la littérature.; POETRY -- American -- General.; American poetry; American poetry -- Mexican American authors; American poetry -- Women authors; Mexican American women in literature; Chicanos; Frauenlyrik; Lyrik; Gedichten.; Vrouwen.; Spaans.; Amerikaans.; Mexicanen.; Chicanos.; 1900-1999; Geschichte 1970-1985.; Criticism, interpretation, etc.